2018
DOI: 10.3892/mmr.2018.8778
|View full text |Cite
|
Sign up to set email alerts
|

miR-185 and miR-29a are similarly expressed in the bronchoalveolar lavage cells in IPF and lung cancer but common targets DNMT1 and COL1A1 show disease specific patterns

Abstract: Idiopathic pulmonary fibrosis (IPF) and lung cancer (LC) constitute two progressively devastating lung diseases with common risk factors including aging and smoking. There is an increasing interest in the investigation of common pathogenic mechanisms between IPF and LC with therapeutic implications. Several oncomirs, microRNAs associated with malignancy, are also linked with IPF. miR-29a and miR-185 downregulation is probably involved both in carcinogenesis and fibrogenesis. We have previously observed miR-29a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Indeed, the expression of miR-29a is reduced both in fibroblasts and skin in SSc (99, 100), and its overexpression induced a reduction of fibroblast proliferation and collagen synthesis in vitro (101). A similar reduced expression of miR-29a has also been found both in broncho-alveolar cells from IPF and lung cancer patients, suggesting a common link between the two conditions (102). Altogether, miR-21 and miR-29 family members exhibit synergistic functions to modulate fibroblast fate both in healthy and fibrotic conditions.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosissupporting
confidence: 61%
“…Indeed, the expression of miR-29a is reduced both in fibroblasts and skin in SSc (99, 100), and its overexpression induced a reduction of fibroblast proliferation and collagen synthesis in vitro (101). A similar reduced expression of miR-29a has also been found both in broncho-alveolar cells from IPF and lung cancer patients, suggesting a common link between the two conditions (102). Altogether, miR-21 and miR-29 family members exhibit synergistic functions to modulate fibroblast fate both in healthy and fibrotic conditions.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosissupporting
confidence: 61%
“…Blocking of both Akt1 and Akt2 reversed the effect, both in culture and in the EBL mouse model, suggesting that both isoforms play an active role in fibrogenesis. This is consistent with results from Bibaki et al, which demonstrated that miR-29a, miR-185, and their targets Akt1 and Akt2, were involved in the development of idiopathic pulmonary fibrosis and lung cancer [53]. However, Lan et al showed that only Akt2 was involved in renal fibrosis [54].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand COL1A1 mRNA levels were increased in interstitial pulmonary fibrosis suggesting a disease‑specific mRNA signature. DNMT1 was downregulated in the lung cancer group and its expression was further reduced in the presence of increasing malignant burden as it was implied by the endobronchial findings 54. The expression levels of FGF2 mRNA and protein in the non-small cell LC tissues were significantly higher than those in the adjacent normal tissues (P<0.001).…”
Section: Molecular Pathwaysmentioning
confidence: 72%